Treatment of wastewater from oil palm industry in Malaysia using polyvinylidene fluoride-bentonite hollow fiber membranes via membrane distillation system - Nor Amirah Safiah, Muhamad; Nadzirah, Mohd Mokhtar; Rosmawati, Naim; Lau, Woei Jye; Nor Hafiza, Ismail (Elsevier Ltd, 2024)
Membrane distillation (MD) is gaining increasing recognition within membrane-based processes for palm oil mill effluent (POME) treatment. This study aims to alter the physicochemical characteristics of polyvinylidene fluoride (PVDF) membranes through the incorporation of bentonite (B) at varying weight concentrations (ranging from 0.25 wt% to 1.0 wt%). Characterization was conducted to evaluate changes in morphology, thermal stability, surface characteristics and wetting properties of the resulting membranes. The resulting membranes were also tested using direct contact membrane distillation (DCMD) with POME as the feed solution, aiming to generate high-purity water. Results indicated that the PVDF-0.3B and PVDF-0.5B membranes achieved the highest water vapor flux. The finger-like structure and macrovoids present in these membranes aid in minimizing mass resistance during vapor transport and enhancing permeate flux. All membranes demonstrated exceptional performance in removing contaminants, eliminating total dissolved solids (TDS) and achieving over 99% rejection of chemical oxygen demand (COD), nitrate nitrogen (NN), color, and turbidity from the feed solution. The permeate water analysis showed that the PVDF-0.3B membrane had superior removal efficiency and met the standards set by the local Department of Environment (DOE). The PVDF-0.3B membrane was chosen as the preferred option because of its consistent flux and high removal efficiency. This study demonstrated that incorporating bentonite into PVDF membranes significantly enhanced their properties and performance for POME treatment.